Deunovism – Doubtfully Attractive andUndoubtfully Dangerous - Sergiev, Ventzislav (Forum Theologicum Sardicense, 2025)
Ventzislav Sergiev, Deunovism – Doubtfully Attractive and Undoubtfully Dangerous. “Deunovism” represents an image of New Age culture. It advocates for a universal religion devoid of dogmas, rules, and institutions, which it views as a form of denying God and depersonalizing humanity. The primary aim of the Orthodox Church is to guide a person towards theosis, a fellowship and union with God, and to transform humanity into God-like beings. In contrast, “Deunovism” seeks to replace the concept of a divine-human relationship with that of a human-God.